The unseen threat: anti-PL7 anti-synthetase mediated interstitial lung disease - Kullar, Maskeen K.; Randhawa, Prabhsimranjeet S.; Nirmal, Jasmine; Singh, Arashdeep; Thukral, Harpreet (International Journal of Research in Medical Sciences, 2025)
Anti-synthetase syndrome (ASS) is a rare autoimmune disorder within the spectrum of idiopathic inflammatory myopathies, defined by the presence of anti-aminoacyl-tRNA synthetase antibodies, most commonly anti-Jo1. Less frequent antibodies, such as anti-PL7, are associated with predominant pulmonary involvement and minimal muscle symptoms. Interstitial lung disease (ILD) is the most serious complication and may be the initial or sole presenting feature. Due to its rarity and atypical manifestations, anti-PL7-associated ASS can be underdiagnosed, especially in elderly patients presenting with unexplained ILD. Herein this case reports the case of a 74-year-old woman who presented with exertional dyspnea and a persistent dry cough for three months. Examination revealed Raynaud’s phenomenon, hyperkeratotic skin changes on the hands (mechanic’s hands), and digital ulceration. Imaging confirmed bilateral ground-glass opacities consistent with ILD. Autoimmune serology showed a positive ANA (1:320, speckled pattern) and anti-PL7 antibody, with no evidence of myositis. Based on Connors et al’s criteria, a diagnosis of anti-synthetase syndrome was made. The patient received high-dose intravenous corticosteroids and cyclophosphamide, with limited clinical improvement. She was discharged on request on long-term oxygen support and oral steroids for outpatient follow-up. This case highlights the diagnostic challenge of ASS, especially when classical myositis features are absent. Anti-PL7-positive patients often present with isolated ILD, carrying a poorer prognosis compared to anti-Jo1-positive patients, and may not respond to standard immunosuppression. Early recognition of dermatologic signs and prompt antibody testing are essential for diagnosis. Aggressive initial therapy may be required, and biologic agents should be considered for refractory cases.